Risk of reactivation of toxoplasmic retinitis following intraocular procedures without the use of prophylactic therapy - Heringer, Gustavo C; Oueghlani, Evelyne; Dell'Omo, Roberto; Curi, André L L; Oréfice, Fernando; Pavésio, Carlos E (British journal of ophthalmology, 2014)
Background/aims Toxoplasmic retinochoroiditis is the commonest known cause of posterior uveitis worldwide and reactivation is unpredictable. Based on results from one study, the authors proposed that antitoxoplasmic therapy should be initiated as prophylaxis for intraocular surgery in patients with toxoplasmic scars. The aim of this study is to analyse the risk of toxoplasmic retinochoroiditis reactivation following intraocular procedures. Methods Retrospective analysis of the medical records of a total of 69 patients who underwent intraocular surgery and presented with toxoplasmic retinochoroiditis scars. Results No patient received prophylactic antitoxoplasmic therapy. Reactivation following the surgical procedure occurred in four cases, with one at 3 months and the others respectively at 13, 14 and 17 months. Conclusions Our study shows that intraocular surgery did not result in a significant reactivation rate of toxoplasmic retinochoroiditis in the absence of preoperative prophylactic antitoxoplasmic therapy.